Randomized interventional clinical trial to estimate the efficacy of clomiphene citrate versus letrozole in induction of ovulation in infertility - Yogindra Kumar Manohar Kabadi; Pavitra S Madinoor (Barpeta Obstetrics and Gynaecological Society, 2022)
Background and objectives: Anovulation accounts for 30-40% of female infertility. The treatment of choice is by ovulation induction. This study is to estimate effectiveness of clomiphene citrate versus letrozole in ovulation induction. Method: 60 women with anovulatory infertility were randomised for treatment with either letrozole or clomiphene citrate for ovulation induction. After a trigger of HCG and coital advice they were observed for ovulation and pregnancy. Results: Ovulation rate was 80% with clomiphene citrate and 93.3% with letrozole. First cycle conception rates with letrozole was higher (23.3%) compared to clomiphene citrate (6.7%). Cumulative conception rate was 25% with clomiphene citrate and 32.1% with letrozole. Pregnancy continuation and miscarriage rates were comparable in both groups. Conclusions: Letrozole is better ovulating agent in infertility compared to clomiphene citrate in terms of monofolliculation and higher endometrial thickness giving good nidation rates than clomiphene citrate. Ovulation rates are comparable with both letrozole and clomiphene citrate but, first cycle conception rates are significantly better with letrozole and even cumulative pregnancy rates were higher with letrozole.